2014
DOI: 10.1097/apo.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Ocular Genetics

Abstract: Purpose To highlight major advancements in ocular genetics from the year 2013. Design Literature review. Methods A literature search was conducted on PubMed to identify articles pertaining to genetic influences on human eye diseases. This review focuses on manuscripts published in print or online in the English language between January 1, 2013 and December 31, 2013. A total of 120 papers from 2013 were included in this review. Results Significant progress has been made in our understanding of the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 114 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…26 Gene variations that alter gene function are more likely to influence phenotypic characteristics, such as the risk of disease. 27 Two SNPs in IL1B, rs1143627 and 32 Ethnic and geographical differences are widely known to be important in evaluating KC pathogenesis. However, the previous study only found rs2071376 in IL1A was associated with KC in Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…26 Gene variations that alter gene function are more likely to influence phenotypic characteristics, such as the risk of disease. 27 Two SNPs in IL1B, rs1143627 and 32 Ethnic and geographical differences are widely known to be important in evaluating KC pathogenesis. However, the previous study only found rs2071376 in IL1A was associated with KC in Chinese.…”
Section: Discussionmentioning
confidence: 99%